2002
DOI: 10.1258/0022215021910069
|View full text |Cite
|
Sign up to set email alerts
|

Medium-term outcome of palatal surgery for snoring using the Somnus™ unit

Abstract: The aim of this study was to retrospectively survey patients who had undergone radiofrequency ablation of the soft palate for snoring complaints. Fifty-nine patients who had undergone radiofrequency ablation were sent an anonymous questionnaire to assess snoring (using visual analogue scales), pain and satisfaction with the procedure. Sixty-one per cent of the group returned the questionnaire. The mean time since operation was 17.5 months. Taking an improvement in snoring of 50 per cent or greater as a success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Follow-up periods were usually 6 to 8 weeks, but especially retrospective trials had a significantly longer follow-up time (2-18 months). 20,22,23 Concerning postoperative complications, no serious adverse events were reported, though it should be mentioned that there was a significant variation in the overall complication rates provided, which ranged from 12,13,18,20 to 50%. 16 The most frequently reported complication was a mucosal erosion or ulceration.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Follow-up periods were usually 6 to 8 weeks, but especially retrospective trials had a significantly longer follow-up time (2-18 months). 20,22,23 Concerning postoperative complications, no serious adverse events were reported, though it should be mentioned that there was a significant variation in the overall complication rates provided, which ranged from 12,13,18,20 to 50%. 16 The most frequently reported complication was a mucosal erosion or ulceration.…”
Section: Resultsmentioning
confidence: 97%
“…Six hundred forty-seven 14 to 704 13 J per treatment session were applied in these cases. If 3 or more lesions were created per session, the mean amount of energy delivered varied between 1099 15 and 2100 22 J. Due to the lack of data in these studies, comparisons concerning the rate of postoperative complications could not be made.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors demonstrated the efficiency of both techniques in eliminating snoring in patients with simple snoring. [8][9][10][11][12][13] Their use in treating OSAS secondary to retropalatal obstruction has gained some popularity but is still not widely accepted. 6,14 The main drawbacks of LAUP and BRVTR of the palate are:…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] Most of these and other published similar studies have utilized technology developed by Somnus ® Medical Technologies, Inc. and have looked at short-term results: more recently it has been shown that medium to long-term results show a signi cant relapse rate. 23 The authors introduce and investigate similar technology developed by Celon ® AG Medical Instruments in a pilot study designed to investigate the results of Celon ® RFTA in simple snorers/mild OSAS. Celon ® proclaims additional bene ts over its rival Somnus ® unit, including inherent bipolar probe tip safety and a shorter procedure time.…”
Section: Introductionmentioning
confidence: 99%